Characteristics of risk factors for acute kidney injury among inpatients administered sulfamethoxazole/trimethoprim: a retrospective observational study - Yuki Shimizu; Toshinori Hirai; Yukari Ogawa; Chihiro Yamada; Emiko Kobayashi (BMC, 2022)
Abstract Background Sulfamethoxazole/trimethoprim (SMX/TMP) potentially increases the serum creatinine levels, resulting in acute kidney injury (AKI). However, the clinical characteristics of the AKI associated with SMX/TMP and the risk factors for its development have not been fully characterized. Methods A retrospective cohort observational analysis was conducted on adult inpatients who started SMX/TMP treatment at the Tokyo Women's Medical University, Yachiyo Medical Center, from April 2018 to March 2020. The primary outcome was AKI, defined as an increase in serum creatinine level of ≥ 50% from baseline. Multivariate logistic regression analysis was used to determine the risk factors for the AKI associated with SMX/TMP. Results Of the 281 patients, 32 (11.4%) developed AKI. The multivariate logistic regression analysis identified that body mass index (BMI) (odds ratio [OR] = 0.86, 95% confidence interval [95% CI] 0.76-0.97, p < 0.01), presence of hypertension (OR = 2.69, 95% CI 1.11-6.49, p = 0.02), SMX/TMP daily dose (OR = 1.16, 95% CI 1.03-1.30, p = 0.02), and concomitant loop diuretic use (OR = 2.91, 95% CI 1.08-7.78, p = 0.04) were the associated risk factors for AKI in patients who were administered SMX/TMP. Conclusions This study showed that low BMI, hypertension, high-dose SMX/TMP, and concomitant loop diuretic use increased the risk of AKI in patients administered SMX/TMP. Clinicians should consider monitoring the renal function in patients at a high risk of AKI.